ESTUDIOS DE DISPERSION DE CONTAMINANTES Y DECLINACION BACTERIANA EN EL MAR DE CHIMBOTE – PERU - SEBASTIÁN CALVO, Carlos (2023)
Dispersion studies and preliminary determinations of bacterial declining (T–90) wereperformed at the bay of Chimbote-Peru. As for the dispersion studies, a fundamentalpartial differential equation and its solution for the three-dimensional case areapplied. The shape and characteristics of the tracer plume is determined as well asthe rate of diminution of peak concentrations. The method considers a point injectionwith Rhodamine B and Iodine 131 as tracers, for determining the longitudinal, lateraland vertical dispersion coefficients that govern the dispersion rates of industrial andwastewaters to discharge through a submarine outfall installed at the sea of Chimbote. The method presented herein allows calculations of dispersion coefficients andpredict the influence of the future diffuser as well, regardless of the nature of thebody of water in which the tests were conducted.In regards to T-90 determinations, they were performed by the use of a combinedtracer technique, using I-131 for dilution measurement and Rhodamine B as a visualaid. Dilution and decrease in bacterial concentrations were taken into considerationas well as continuous radiotracer injection.